2018
DOI: 10.1136/emermed-2018-207881
|View full text |Cite
|
Sign up to set email alerts
|

Use of scratchcards for allocation concealment in a prehospital randomised controlled trial

Abstract: BackgroundRapid Analgesia for Prehospital Hip Disruption was a small study designed to determine the feasibility of undertaking a randomised controlled trial (RCT) to test the clinical and cost-effectiveness of paramedics administering Fascia Iliaca Compartment Block as early prehospital pain relief to patients with a fractured hip. The objective was to devise a simple and effective method of random allocation concealment suitable for use by paramedics while in the emergency prehospital setting.MethodsScratchc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…We recruited and trained 19 paramedics based at ambulance stations in the catchment area of one ED in South Wales. They used scratch cards to randomly allocate eligible patients with suspected hip fracture to receive FICB or normal care 17…”
Section: Methodsmentioning
confidence: 99%
“…We recruited and trained 19 paramedics based at ambulance stations in the catchment area of one ED in South Wales. They used scratch cards to randomly allocate eligible patients with suspected hip fracture to receive FICB or normal care 17…”
Section: Methodsmentioning
confidence: 99%
“…We recruited and trained 19 paramedics based at ambulance stations in the catchment area of one emergency department in South Wales to administer FICB to patients with suspected hip fracture. A participating emergency paramedic who attended a 999 call and identified a hip fracture in an eligible patient then used a scratchcard42 to randomly allocate the individual to receive FICB (if not contra-indicated) or usual care. Full RAPID results are available 19…”
Section: Methodsmentioning
confidence: 99%
“…A randomisation schedule with a 1:1 ratio of ‘intervention’ or ‘control’, stratified by paramedic was produced by a statistician not involved in the data collection, management or analysis of the data set. A unique set of scratchcards with allocation concealed was issued to each study paramedic and kept on their person during each working shift 19 . When the study paramedic identified an eligible patient, they were instructed to use the next sequential scratchcard from their set out of sight of the patient.…”
Section: Methodsmentioning
confidence: 99%